"Nothing without Neighbours" – Campanilistic Narratives of Island Communities in Oral Traditions - Škrbić Alempijević, Nevena (Array, 2013)
The Croatian islands of Hvar and Brač feature a diversified system of rivalry and animosity between different island communities, which can be defined by the term campanilism. This is based on stereotypes about inhabitants of neighbouring island communities or neighbouring islands and on the production of derisive collective nicknames. Anecdotes, jokes, proverbs, and similar oral forms are used to confirm characteristics attributed to certain island communities. Nowadays, the performance of this animosity is mainly connected to sporting events, celebrations of patron saints’ days, and school children’s disputes. Previously, they were considered to be exclusively local, intra-island heritage. Islanders have generally found these traditions insulting and mocking, which has triggered emotional responses. However, some island communities have recently decided to turn these stereotypes into brands, highlighting them in representations of local identities and in tourist promotion. In this presentation, we will analyse how certain stereotypes focusing on islanders’ flaws (gluttony, parsimony) or virtues (cohesion, industriousness) are used in contemporary identity strategies and in the construction of local uniqueness. Oral traditions and their performances are approached as important dimensions of this process.